A novel surgical procedure for medial canthal fistula closure in midline destructive lesions: two case reports - Ishai, Meydan Ben; Kaur, Simerdip; Oliphant, Huw; Rajak, Saul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Medial canthal fistula in the context of destructive processes poses a significant surgical challenge. We report the closure of the fistula using a novel Back-to-Back Sandwich Flap (B2BSF) in two patients. The surgery involves fashioning a paired inner layer inverted local skin flap covered by an outer layer skin glabellar to create a double layer back-to-back flap to cover the defect. It was used to close a 2.5 by 2.5 mm fistula in one patient with CIMDL and a 0.5 by 1 mm in a second patient with radiotherapy damage post-SCC. Three months post-surgery, the fistula remained closed in both patients. Medial canthal fistula can compromise the ocular surface and vision and is unsightly and uncomfortable. It is difficult to close the fistula, particularly in a destructive process with unhealthy and avascular surrounding tissue. The B2BSF appears to be an effective surgical reconstructive strategy for this challenging situation.